A biphasic Mercury-ion sensor: exploiting microfluidics to make simple anilines competitive Ligands - Petzoldt, Martin; Eschenbaum, Carsten; Schwaebel, S. Thimon; Brödner, Kerstin; Lemmer, Uli; Hamburger, Manuel; Bunz, Uwe H. F. (Chemistry - a European journal, 2015)
Abstract Combining the molecular wire effect with a biphasic sensing approach (analyte in water, sensor-dye in 2-methyltetrahydrofuran) and a microfluidic flow setup leads to the construction of a mercury-sensitive module. We so instantaneously detect Hg2+ ions in water at a 500??M concentration. The sensor, conjugated non-water soluble polymer 1 (XFPF), merely supports dibutylaniline substituents as binding units. Yet, selective and sensitive detection of Hg2+-ions is achieved in water. The enhancement in sensory response, when comparing the reference compound 2 to that of 1 in a biphasic system in a microfluidic chip is >103. By manipulation of the structure of 1, further powerful sensor systems should be easily achieved.
Gesehen am 03.07.2020